2010
DOI: 10.1155/2011/692378
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Antidiabetic Role of Parkinsonia aculeata (Caesalpineaceae)

Abstract: This paper reports the characterization of the antidiabetic role of a hydroethanolic extract from Parkinsonia aerial parts (HEPA), in normal and alloxan-induced diabetic rats, treated with HEPA (125 and 250 mg/kg; p.o.). Oral glucose tolerance test, acute oral toxicity test and preliminary phytochemical analyses were performed. The diabetic rats treated with HEPA showed a significant reduction in serum and urinary glucose, urinary urea and triglyceride levels, as compared to the diabetic untreated group. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 52 publications
0
10
0
2
Order By: Relevance
“…The final yield of the hydroethanolic extract partitioned with ethyl acetate of P. aculeata aerial parts (HEPa/EtOAc) was 5.2/50 g of the dried powdered aerial parts. Based on three previous studies by our group [10,11,15], for pharmacological assays, a fresh dilution of lyophilized HEPa/EtOAc extract in vehicle (distilled water) was prepared on the day of treatment and administered by gavage at the doses of 125 and 250 mg/kg b.w. in a fixed volume of 0.2 mL.…”
Section: Preparation Of Plant Extractmentioning
confidence: 99%
See 2 more Smart Citations
“…The final yield of the hydroethanolic extract partitioned with ethyl acetate of P. aculeata aerial parts (HEPa/EtOAc) was 5.2/50 g of the dried powdered aerial parts. Based on three previous studies by our group [10,11,15], for pharmacological assays, a fresh dilution of lyophilized HEPa/EtOAc extract in vehicle (distilled water) was prepared on the day of treatment and administered by gavage at the doses of 125 and 250 mg/kg b.w. in a fixed volume of 0.2 mL.…”
Section: Preparation Of Plant Extractmentioning
confidence: 99%
“…In this regard, the present study demonstrates that P. aculeata is effective in improving insulin resistance in a mouse model of obesity and this effect seems to involve the antioxidant mechanisms through the increase in PPARc/ CuZn-SOD axis expression. In addition to these important effects, we can assume that P. aculeata is toxicologically safe, since a previous study has demonstrated that the oral administration of a maximum dose of 5 g/kg of HEPa/ EtOAc did not result in any lethality or observable behavioral changes [10].…”
Section: Data Presented By the World Health Organization (Who)mentioning
confidence: 99%
See 1 more Smart Citation
“…It have been reported that herbal remedies may have recognizable therapeutic effects [1]. However, some species of plants have been reported to have hypoglycemic effects; hence, attention has been given to find biologically active compounds from various medicinal plants as a source of natural antidiabetic drugs [2,3,4]. However, only few of these plant have been reported Petersianthus macrocarpus belongs to the family Lecythidaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Though different types of oral hypoglycemic agents are available for the treatment of diabetes mellitus, there is increasing demand by patients to use antidiabetic natural products because of the undesirable side effects of the existing drugs. In many countries, much attention has been paid to find novel type of natural antidiabetic drugs from various medicinal plants [ 2 5 ]. With thousands of years of medical practice, a great deal of valuable experience has been accumulated in traditional Chinese medical system for diabetic therapy and several herbs have been used to improve the hyperglycemic condition in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%